Piebald lethal (sl) acts early to disrupt the development of neural crest-derived melanocytes. - Pavan, W J (1994)
Mice homozygous for the piebald lethal (sl) mutation have a predominantly white coat due to the absence of neural crest-derived melanocytes in the hair follicles. To investigate the time in embryonic development when the s1 gene affects the melanocyte lineage, we compared the distribution of melanocyte precursors in wild-type and mutant embryos, using an antibody specific for tyrosinase-related protein 2 (TRP-2). TRP-2 positive cells were first observed adjacent to the anterior cardinal vein in 10.5-day postcoitem wild-type embryos. From 11.5 to 13.5 days postcoitem, there was a nonuniform distribution of TRP-2 positive cells along the anterior-posterior axis, with the highest density of cells in the head and tail regions. Along the dorsal-ventral axis, the cells were restricted to positions lateral, but never dorsal, to the neural tube. In homozygous sl/sl embryos TRP-2 staining was restricted to the non-neural crest-derived melanocytes of the pigmented retinal epithelium and the telencephalon. Few positive cells were seen in areas that will form neural crest-derived melanocytes in the inner ear, skin, hair follicles, leg musculature, or heart. We conclude that the piebald lethal mutation acts prior to the onset of TRP-2 expression to disrupt the development of neural crest-derived melanocytes. The non-uniform distribution of melanoblasts in wild-type mice suggests that piebald acts stochastically to affect melanocyte development.